Impact of prolonged postoperative antibiotic administration on postoperative complications in elderly patients undergoing colorectal cancer surgery - Park, Go Woon; Park, Nahyeon; Kuk, Jung Chul; Lim, Dae Ro; Shin, Eung Jin (Frontiers in Surgery, 2026)
ProposeThe purpose of this study was to investigate whether prolonged antibiotic usage beyond conventional practices could impact the incidence of postoperative complications in elderly patients undergoing colorectal cancer surgery.Materials and methodsBetween January 2016 and December 2022, a total of 292 patients aged over 70 years who underwent curative resection for colorectal cancer were identified from a retrospective database. The study population was divided into two groups: the POD#1 group, consisting of patients who received postoperative antibiotics for 1 day (n = 214), and the POD#3 group, comprising patients who received postoperative antibiotics for at least 3 days (n = 78).ResultsA significant difference between two groups was observed in the rates of total postoperative complications, infection-related complications and antibiotic reuse. In the POD#1 group, complications occurred at a rate of 25.7% (n = 55), while the POD#3 group showed a lower complication rate of 14.1% (n = 11) (p = 0.036). The infection-related complications such as anastomotic leakage, wound infection, pneumonia occurred at a rate of 20.1% (n = 43) in POD#1 group compared to 5.1% (n = 4) in POD#3 group (p = 0.002). The antibiotic re-use rate was 22.4% (n = 48) in the POD#1 group and 11.5% (n = 9) in the POD#3 group (p = 0.038). In the multivariate analysis, ASA score (HR 1.79; 95% CI 1.09–2.97; p-value = 0.022) and postoperative antibiotic usage (HR 0.49; 95% CI 0.26–0.94; p-value = 0.032) emerged as independent risk factors for postoperative complications.ConclusionIn colorectal cancer patients over the age of 70, prolonged antibiotic usage demonstrated a reduction in the rate of postoperative complications, including anastomotic leakage. Considering the potentially fatal consequences of postoperative complications in the elderly, the advantages of extended antibiotic administration beyond conventional usage outweigh the concerns regarding complications or costs associated with antibiotics use.